On the Dynamic Foundation of Evolutionary Stability in Continuous Models - Jörg Oechssler; Frank Riedel (University of Bonn, Bonn Graduate School of Economics (BGSE), 2000)
We show in this paper that none of the existing static evolutionary stability concepts (ESS, CSS, uninvadability, NIS) is sufficient to guarantee dynamic stability in the weak topology with respect to standard evolutionary dynamics if the strategy space is continuous. We propose a new concept, evolutionary robustness, which is stronger than the previous concepts. Evolutionary robustness ensures dynamic stability for replicator dynamics in doubly symmetric games.
Keywords: C70; C72; 330; replicator dynamics; evolutionary stability; ESS; CSS